2021
DOI: 10.1007/s00535-021-01760-9
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-associated liver injury: from bedside to bench

Abstract: The outbreak of coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has been a global challenge since December 2019. Although most patients with COVID-19 exhibit mild clinical manifestations, in approximately 5% of these patients, the disease eventually progresses to severe lung injury or even multiorgan dysfunction. This situation represents various challenges to hepatology. In the context of liver injury in patients with COVID-19, several key problems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
57
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 100 publications
(164 reference statements)
0
57
0
1
Order By: Relevance
“…Liver injury emerges as a co-existing symptom in COVID-19 [ 126 ] and it might result from direct viral toxicity, but also from an overproduction of cytokines and/or NETs [ 127 ]. In patients with COVID-19 injured liver displays patchy necrosis alike in experimental models of the net-damaged liver [ 128 , 129 ].…”
Section: Nets’ Impact At the Organ Levelmentioning
confidence: 99%
“…Liver injury emerges as a co-existing symptom in COVID-19 [ 126 ] and it might result from direct viral toxicity, but also from an overproduction of cytokines and/or NETs [ 127 ]. In patients with COVID-19 injured liver displays patchy necrosis alike in experimental models of the net-damaged liver [ 128 , 129 ].…”
Section: Nets’ Impact At the Organ Levelmentioning
confidence: 99%
“…The main target organ of SARS-CoV-2 infection is not only the lung but also many extrapulmonary tissues[ 3 ]. Among them, COVID-19 combined with liver injury has become a very prominent clinical problem and has garnered great attention[ 4 ]. The author of this article once reported that about one-fifth of the 48 COVID-19 patients have abnormal liver function[ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another problem is the study of pathogenesis. It is necessary to determine whether SARS-CoV-2 can directly invade the liver, especially when angiotensin-converting enzyme 2 (ACE2) appears to be negligibly expressed on liver cells[ 4 ]. In addition, the mechanisms underlying liver dysfunction in COVID-19 patients are not fully understood; it may be multifactorial and related to hyperinflammation, dysregulated immune responses, abnormal coagulation, and drugs[ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 binds to the human cells via Angiotensin-Converting Enzyme 2 (ACE2), which is expressed in the liver and lungs [4][5][6]. Interestingly, ACE2, which serves as the host cell receptor of SARS-CoV-2, plays a protective role against liver and lung damage and is expressed in hepatocytes [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%